Methods for the Synthesis of Digital Controllers for an Asynchronous Brushless Motor - Jumaev, O. A.; Sayfulin, R. R.; Samadov, A. R.; Arziyev, E. I.; Jumaboyev, E. O. (New Visions in Science and Technology Vol. 9, 2021)
The problems of optimizing the operating modes of an asynchronous electric drive according to the criterion of minimum stator current, as well as the optimal control system for an induction motor with a reference rotor flux linkage vector, which can be used for most serial frequency converters, are added to the control channel of the longitudinal component of the stator current.